The effectiveness of RISDA supplementary economics support to smallholders / Mohd Saifuzi Abd Rahim - Abd Rahim, Mohd Saifuzi (Faculty of Business and Management, 2009)
In this project paper, the aim of this research is to study the effectiveness of RISDA supplementary economics support to smallholders. This research involves smallholders from three district areas of Melaka who get the supplementary economics support from RISDA. Three factors have been used to determine the effectiveness of RISDA supplementary economics support to smallholders. This study is about the relationship of the management support, material support and smallholder’s attitude with the effectiveness of support given by RISDA to smallholders. Multiple regressions method, one way ANOVA and correlation was conducted to complete the objectives in this study. From the result, found that, smallholder’s attitude has strong relationship with the effectiveness of the supplementary economics support given by RISDA to smallholders.